Tebipenem as an oral alternative for the treatment of typhoid caused by XDR Salmonella Typhi. (17th September 2021) - Mylona, Elli; Voong Vinh, Phat; Qureshi, Sonia; Karkey, Abhilasha; Dongol, Sabina; Ha Thanh, Tuyen; Walson, Judd; Ballell, Lluis; Fernández Álvaro, Elena; Qamar, Farah; Baker, Stephen
Abstract: Background: Antimicrobial therapy is essential for the treatment of enteric fever, the infection caused by Salmonella serovars Typhi and Paratyphi A. However, an increase in resistance to key antimicrobials and the emergence of MDR and XDR in Salmonella Typhi poses a major threat for efficacious outpatient treatments. Objectives: We recently identified tebipenem, an oral carbapenem licensed for use for respiratory tract infections in Japan, as a potential alternative treatment for MDR/XDR Shigella spp. Here, we aimed to test the in vitro antibacterial efficacy of this drug against MDR and XDR typhoidal Salmonella . Methods: We determined the in vitro activity of tebipenem in time–kill assays against a collection of non-XDR and XDR Salmonella Typhi and Salmonella Paratyphi A (non-XDR) isolated in Nepal and Bangladesh. We also tested the efficacy of tebipenem in combination with other antimicrobials. Results: We found that both XDR and non-XDR Salmonella Typhi and Salmonella Paratyphi A are susceptible to tebipenem, exhibiting low MICs, and were killed within 8–24 h at 2–4×MIC. Additionally, tebipenem demonstrated synergy with two other antimicrobials and could efficiently induce bacterial killing. Conclusions: Salmonella Paratyphi A and XDR Salmonella Typhi display in vitro susceptibility to the oral carbapenem tebipenem, while synergistic activity with other antimicrobials may limit the emergence of resistance. The broad-spectrum activity of this drug against MDR/XDR organisms renders tebipenem a good candidate for clinical trials.